PEMBINAAN DENGAN PEMBERIAN CONTOH LATIHAN KONTROL KERJA MANDIRI YANG TERPROGRAM UNTUK PEMBUATAN RPPH DAPAT MENINGKATKAN KOMPETENSI GURU TK GUGUS ANGGREK DI TK PERMATA MAHKOTA KEC. RAMBAH KAB. ROKAN HULU - ., Eridawati (Edu Research, 2017)
Preparation of the implementation plan of learning is very important, because the management of good learning is very influential on the preparation of the implementationÂ  plan of learning according to indicators. CLKK excellence is exemplified in the manufacture of teachers RPPH and then practice with supervision and activities that do not rely on others. This research uses descriptive qualitative approach, while the technique used in data collection method is observation technique and interview technique. While the research instrument used in this study developed the instrument of observation guidance in the coaching program from beginning to end on each cycle. CLKK coaching model in the coaching program can improve the competence of Gugus Anggrek TK teacher in Kecamatan Rambah. The success of teachers to develop their competence on the making of RPPH and implementation in class based on the value then the success is in Cycle I 37.03%, Cycle II 81.48% and 100% cycle III.